Clinical and Laboratory Urinary Tract Infections in Children Treated at The Children's Hospital Ward Raden Mattaher Jambi from May to August in 2013 - setiamal, dhody (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2013)
This study to determine the clinical features and laboratory urinary tract infections in children admitted to the pediatric ward Hospital Raden Mattaher Jambi from May to August in 2013. This is a prospective descriptive study involving 27 patients who were treated urinary tract infection in children's hospital wards Raden Mattaher Jambi. The results of this study found a total of 51.9% occurred in the male gender with preschool age or age group 7-12 years 48.1%, 92.6% as fever, erythrocyte> 5/Lpb 33.3%, leukocyte > 5/Lpb 25.9%, and 48.1% of E. coli bacteria mos